Retrospective serological analysis reveals presence of the emerging lagovirus RHDV2 in Australia in wild rabbits at least five months prior to its first detection. Issue 2 (13th November 2019) - Strive, Tanja; Piper, Melissa; Huang, Nina; Mourant, Roslyn; Kovaliski, John; Capucci, Lorenzo; Cox, Tarnya E.; Smith, Ina
Abstract: The lagovirus rabbit haemorrhagic disease virus (RHDV) has been circulating in Australia since the mid‐1990s when it was released to control overabundant rabbit populations. In recent years, the viral diversity of different RHDVs in Australia has increased, and currently four different types of RHDV are known to be circulating. To allow for ongoing epidemiological studies and impact assessments of these viruses on Australian wild rabbit populations, it is essential that serological tools are updated. To this end, reference sera were produced against all four virulent RHDVs (RHDV, RHDV2 and two different strains of RHDVa) known to be present in Australia and tested in a series of available immunological assays originally developed for the prototype RHDV, to assess patterns of cross‐reactivity and the usefulness of these assays to detect lagovirus antibodies, either in a generic or specific manner. Enzyme‐linked immunosorbent assays (ELISAs) developed to detect antibody isotypes IgM, IgA and IgG were sufficiently cross‐reactive to detect antibodies raised against all four virulent lagoviruses. For the more specific detection of antibodies to the antigenically more different RHDV2, a competition ELISA was adapted using RHDV2‐specific monoclonal antibodies in combination with Australian viral antigen. Archival serum banks from a long‐term rabbit monitoring site where rabbits were sampled quarterly over a period of 6 years were re‐screened using this assay and revealed serological evidence for the arrival of RHDV2 in this population at least 5 months prior to its initial detection in Australia in a dead rabbit in May 2015. The serological methods and reference reagents described here will provide valuable tools to study presence, prevalence and impact of RHDV2 on Australian rabbit populations; however, the discrimination of different antigenic variants of RHDVs as well as mixed infections at the serological level remains challenging.